Study of the process of thermal dissociation of tantal pentachloride in vacuum - Polyakov, Yu.I.; Rudenkyi, S.G.; Lukirsky, Yu.V.; Konovalov, I.I.; Rak, V.I. (Вопросы атомной науки и техники, 2019)
The dependence of the degree of dissociation of TaCl₅α(T, P) vapors on the temperature in the range of 1470...1820 K in a vacuum of 1.33·10⁻² Pa was by using of equilibrium chemical thermodynamics obtained. The experimental data on the dependence of αex(Т, Р) on temperature and vapor mass flow TaCl₅ were analyzed and compared with calculations. У рамках рівноважної хімічної термодинаміки отримана залежність ступеня дисоціації парів TaCl₅α(T, P) від температури в інтервалі 1470…1820 К і вакуумі 1,33·10⁻² Па. Проаналізовано та порівняно з розрахунковими експериментальні дані залежності αексп(Т, Р) від температури і масового потоку парів TaCl₅. В рамках равновесной химической термодинамики получена зависимость степени диссоциации паров TaCl₅α(T, P) от температуры в интервале 1470…1820 К и вакууме 1,33·10⁻² Па. Проанализированы и сравниваются расчетные данные с экспериментальными данными зависимости αэксп(Т, Р) от температуры и массового потока паров TaCl₅.